Legal and Ethical Policies for Human Brain-Computer Interfaces Storage in The Cloud Era: Privacy Rights Protection and Neurological Data Treatment - Antonio Guterres; Lufiano Tilman Martins; Salustiano Quintão de Carvalho (Politeknik Siber Cerdika Internasional, 2026)
This study examines the legal and ethical implications of storing human brain memory through Brain–Computer Interfaces (BCIs) integrated with cloud systems, with a focus on privacy rights protection and neurological data governance. Using a qualitative research design with a juridical-normative and technological ethics approach, this study analyzes regulatory gaps, ethical challenges, and technological risks associated with neurodata. Data were obtained through a literature review, normative legal analysis, and a comparison of international data protection frameworks. The findings reveal three key issues: the absence of specific legal regulations governing neurodata as a super-sensitive category; ethical concerns related to mental rights, cognitive autonomy, and the potential misuse of memory data; and technological vulnerabilities, including security breaches, unauthorized access, and commercial exploitation of neurodata by cloud service providers. The study argues that neurodata requires a dedicated regulatory framework supported by strict ethical principles and sophisticated security mechanisms. The study concludes that a comprehensive policy combining legal standards, ethical safeguards, and technological safeguards is urgently needed to ensure that cloud-based BCI systems do not compromise human dignity, mental integrity, and fundamental privacy rights.